2015
DOI: 10.1039/c5cs00541h
|View full text |Cite
|
Sign up to set email alerts
|

In vivo delivery, pharmacokinetics, biodistribution and toxicity of iron oxide nanoparticles

Abstract: Iron oxide nanoparticles (IONPs) have been extensively used during the last two decades, either as effective bio-imaging contrast agents or as carriers of biomolecules such as drugs, nucleic acids and peptides for controlled delivery to specific organs and tissues. Most of these novel applications require elaborate tuning of the physiochemical and surface properties of the IONPs. As new IONPs designs are envisioned, synergistic consideration of the body's innate biological barriers against the administered nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
586
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 696 publications
(608 citation statements)
references
References 369 publications
(621 reference statements)
16
586
0
6
Order By: Relevance
“…The focus of current research on SPIONs includes their biodistribution and pharmacokinetics in order to better understand how they function as a carrier as well as to minimize any negative side effects such as toxicity. [48] The magnetic properties of SPIONs are size-dependent. The surface chemistry of SPIONs is another influential factor on their properties such as the extent of immune response they induce.…”
Section: Superparamagnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of current research on SPIONs includes their biodistribution and pharmacokinetics in order to better understand how they function as a carrier as well as to minimize any negative side effects such as toxicity. [48] The magnetic properties of SPIONs are size-dependent. The surface chemistry of SPIONs is another influential factor on their properties such as the extent of immune response they induce.…”
Section: Superparamagnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…The surface chemistry of SPIONs is another influential factor on their properties such as the extent of immune response they induce. [48][49][50] Therefore, research on different coatings for SPIONs has been conducted since a typical SPION has a hydrophobic surface and tend to agglomerate. Chitosan and PEG are two organic polymers that are used to help modify the surface chemistry of SPIONs.…”
Section: Superparamagnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Hamed Arami et al reported that the effects of size, various additional molecular parameters on the surface of the iron oxide nanoparticles, molecular structure of the coating molecules, administered dose on their degradation rates, and transformation to plasma ferritin still require to be studied systematically in more accurate ways through developed characterization tools with higher mass sensitivities [26]. Our lab continuously and systematically studied the nanotoxicity of iron oxide nanoparticles coated with dimercaptosuccinic acid (DMSA), which possessed a mean particle size of 11 nm through TEM observation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, with the development of nanotechnology, nanomaterials are widely investigated and applied in many¯elds, such as biomedicine, cosmetics, catalysis, food, textiles, semiconductors, and biomedicines. [2][3][4][5] In addition to occupational exposure, direct human bodies exposures through commercial applications and ambient air pollution were a major concern.…”
Section: Introductionmentioning
confidence: 99%